Analysis of caesarean section in a tertiary care hospital, Assam, India - Banerjee, Alaka; Bhadra, Banasree; Dey, Kiriti R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: One of the commonest surgery performed worldwide is caesarean Section (CS). The World Health Organization (WHO) has identified an ideal caesarean section (CS) rate for a nation of around 10-15%. In recent times the proportion of delivery conducted by caesarean section has increased. Methods: This is a retrospective study of all the caesarean deliveries performed between 1st January 2010 to 31st December 2018 in the Department of Obstetrics and Gynaecology in Silchar Medical College. The caesarean rate was calculated as: (total number of caesarean deliveries/ total number of deliveries) × 100. The indications for CS included foetal distress, malpresentation, previous caesarean section, multiple gestation, failed induction, failed progression, cephalopelvic disproportion, maternal indications, obstetric indication and foetal indications. Results: During the study period a total of 75685 patients delivered. 25805 patients had undergone CS with the CS rate being around 34.1%. Majority of the CS (75.6%) were performed as emergency procedure. Maximum number of patients were between 21-30 years (73.24%) and 54.47% were primipara. Majority of the patients (68.37%) belonged to the rural areas. Foetal distress (32.8%) was the commonest indication followed by post caesarean pregnancy (26.76%). Conclusions: The rate of caesarean section is increasing with time. As primary caesarean section usually determines the lady’s future obstetric course, it is of prime importance to give effort for safe reduction of caesarean. Individualization of the indication and careful evaluation, following standardized guidelines and practice of evidenced-based obstetrics followed by audits in the institution, can help us limit the caesarean rates.